Self-perception of learning in tourism students of generation Z - Berzunza-Criollo, Milton (2023)
This research was carried out at the Universidad de Oriente (UNO) in Mexico with first-year students of the Bachelor's Degree in Tourism Development, its objective is to establish the self-perception of one's own generation and its relationship with learning and teaching. of their teachers. The study was qualitative with a phenomenological design, using the focus group technique, with convenience sampling, whose participants voluntarily attended the interviews. It was obtained that the students understand why their teachers teach with different strategies from the way in which they consider they learn, and it is due to the generation gap and their condition of digital migrants, being the conception and use of technology the main one. difference between them. Among the scope of the study is that it applies exclusively to students from the Yucatecan context and UNO, so it is desirable to replicate it with other students of this generation. It is concluded that there are significant differences between the methodologies of the teaching-learning process between students and their teachers, which impacts the way of teaching and learning, since they use materials that may not be entirely useful for understanding the contents of the subjects.